Antibacterial and Alteration of Drug Resistance Activities of Black Cumin Seed (Nigella Sativa) Extracts against Urinary Pathogens - Al Dosary, Reem Abdulaziz Al Qannam (Journal of Public Health Sciences, 2023)
Most urinary pathogens that cause urinary tract infection (UTI) have developed multidrug-antibiotic resistance (MDR) and forewarned our research interest in investigating natural products to increase medicinal plant usage as alternative therapies for infectious diseases.  This study was carried out to investigate the antibacterial activities of ethanolic extract from black cumin seeds (Nigella sativa), which were evaluated by minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) assays against clinically isolated MDR urinary pathogens and compared with E.coli ATCC 35218. In this study, the ethanol extract of Nigella sativa possesses strong microbial growth inhibitory effects against the tested pathogens. The inhibitory activity of ethanolic extract (EE) was more robust with dose-dependent inhibitory effects. The minimum MIC values were observed for Proteus mirabilis (1.5 mg/ml), followed by Pseudomonas aeruginosa (2 mg/ml), extended-spectrum β-lactamase (ESBL) producing Klebsiella pneumonia (2.5 mg/ml), ESBL producing Escherichia coli(2.75 mg/ml)and Acinetobacter baumannii(2.5 mg/ml).MBC inhibitory effects of ethanolic extracts were more significant than those of corresponding MIC results for all clinically isolated urinary pathogens. The bactericidal values of ethanol extracts were slightly increased than the related MIC. All the data was compared with E.coli ATCC 35218. This study augmented the effective antibacterial activity of Niofla sativa seed extract against carbapenem-resistant E. coli and Klebsiella pneumonia clinical isolates. Thus, it might be an effective potential source of safe and natural antimicrobial agents against emerging ESBL-producing clinical isolates.